Analisis Faktor Penyebab Asfiksia Pada Bayi Baru Lahir Di Rsud Siti Aisyah Kota Lubuklinggau - Yulita Elvira Silviani; Desi Fitriani; Mika Oktarina; Ovianis Danti; Ida Rahmawati (Jurnal Kesehatan Medika Udayana, 2022)
Background : Asphyxia neonatorum is an emergency in infants caused by a lack of oxygen supply and an increase in carbon dioxide in the lungs which results in death. Good antenatal care and delivery assistance by health workers are highly recommended for early detection and treatment of obstetric complications that may occur in pregnant women and newborns. The purpose of this research is Studi analysis of the factors causing asphyxia in newborns at the Siti Aisyah Hospital. Methods: This study uses an analytical survey method with a case control approach.The sampling technique in this study used systematic random sampling, the samples in this study was 206 Respondens. Analysis data used univariate and bivariate analysis. statistical test using chi square. Results: The results of the study showed that there was a relationship between preeclampsia, premature delivery, post-term delivery, and the second (two) long stage with the incidence of asphyxia in newborns with a value of 0.000, this value < 0.05. Conclusion: Asphyxia neonatorum is serious and threatens the baby's life, so good knowledge is needed for mothers in routinely carrying out antenatal care and assisting health workers for pregnant women who check their wombs.